Radiological presentation of active pulmonary tuberculosis in kidney transplant recipients: a retrospective study of four cases and a review of the literature - Oliveira, Virgilio de Araujo [UNESP]; Almeida, Ricardo Augusto Monteiro de Barros [UNESP]; Cavalcante, Ricardo de Souza [UNESP]; de Andrade, Luis Gustavo Modelli [UNESP]; Ribeiro, Sergio Marrone [UNESP] (FapUNIFESP (SciELO), 2024)
Although kidney transplantation is the best therapeutic option for patients with chronic kidney disease, the immunosuppression required greatly increases susceptibility to infections that are responsible for high post-transplant mortality. Pulmonary tuberculosis (TB) represents a major cause of such infections, and its early diagnosis is therefore quite important. In view of that, we researched the manifestations of active pulmonary TB in kidney transplant recipients, through chest X-ray and computed tomography (CT), as well as determining the number of cases of active pulmonary TB occurring over a 3.5-year period at our institution. We identified four cases of active pulmonary TB in kidney transplant recipients. The CT scans provided information complementary to the chest X-ray findings in all four of those cases. We compared our CT findings with those reported in the literature. We analyzed our experience in conjunction with an extensive review of the literature that was nevertheless limited because few studies have been carried out in low-and middle-income countries, where the incidence of TB is higher.
Apresentação radiológica da tuberculose pulmonar ativa em transplantados renais: um estudo retrospectivo de quatro casos e revisão da literatura
Keywords: Immunosuppres-sive agents/adverse effects; Kidney transplantation; Opportunistic infections; Radiography, thoracic; Tomography, X-ray computed; Tuberculosis, pulmonary